1995
DOI: 10.2527/1995.733738x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and body composition of Meishan and Yorkshire barrows and gilts2

Abstract: Five barrows and five gilts of each of two breeds (Meishan [Ms] and Yorkshire [Y]) were slaughtered at birth and at 41, 71, 123, and 171 d of age and five gilts of each breed were slaughtered at 260 d of age. Major organ and visceral weights were obtained immediately postmortem (PM), whereas carcass characteristics, carcass composition, femur measurements, and two individual muscle weights were obtained 24 h PM. Linear and quadratic regression coefficients on age differed between the two breeds, in favor of Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
36
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 25 publications
10
36
0
1
Order By: Relevance
“…Carr et al (1978) and Correa et al (2006) also reported that the total lean, fat and bone content increased with slaughter weight. In addition, developmental changes of carcass lean percentage in the two breeds are in agreement with previous reports (Shields et al, 1983;Ferrell and Cornelius, 1984;White et al, 1995), who observed that empty body protein and fat-free carcass lean percentages increase from birth to approximately 45 to 65 kg as percentage of water decrease. Xu (1994) found that the Jinhua pig is an early-maturing type, which had higher percentages of body fat.…”
Section: Discussionsupporting
confidence: 92%
“…Carr et al (1978) and Correa et al (2006) also reported that the total lean, fat and bone content increased with slaughter weight. In addition, developmental changes of carcass lean percentage in the two breeds are in agreement with previous reports (Shields et al, 1983;Ferrell and Cornelius, 1984;White et al, 1995), who observed that empty body protein and fat-free carcass lean percentages increase from birth to approximately 45 to 65 kg as percentage of water decrease. Xu (1994) found that the Jinhua pig is an early-maturing type, which had higher percentages of body fat.…”
Section: Discussionsupporting
confidence: 92%
“…The higher lipid accretion in Jinhua pigs is probably related to an increase in extra energy available for lipid synthesis. Similar results were reported when Meishan (White et al, 1995), Iberian pigs (Morales et al, 2003) or Creole pigs (Renaudeau and Mourot, 2007) were compared to conventional lean pigs. In addition, carcass fat content increased with age in the two breeds.…”
Section: Discussionsupporting
confidence: 77%
“…Barrows had higher average daily gains and higher average daily feed intakes than gilts (Table 2), which is consistent with most reports in the literature (White et al 1995). However, the gain:feed ratio was not different between the sexes.…”
Section: Growth Performance and Carcass Characteristics Of Progenysupporting
confidence: 82%
“…However, growth rates were numerically lower in pigs from the Meishan lines (P = 0.14) and further study is required to establish the growth performance of one-eighth Meishan slaughter pigs compared to conventional lines. Other studies have reported that purebred Meishan, one-half Meishan, and one-quarter Meishan crossbred pigs have reduced growth rates with a lower feed efficiency than western breeds of pigs (Haley et al 1992;Bidanel et al 1993;Mercer and Hoste 1994;White et al 1995;Young 1995b). However, Young (1998b) found no differences in the growth rate and feed efficiency between one-eighth Meishan and seveneighths white cross and one-eighth Duroc and seven-eighths white cross lines, results that are similar to those of the current study.…”
Section: Growth Performance and Carcass Characteristics Of Progenymentioning
confidence: 99%